Increasing smoking cessation care across a network of hospitals: an implementation study. (December 2015) - Slattery, Carolyn; Freund, Megan; Gillham, Karen; Knight, Jenny; Wolfenden, Luke; Bisquera, Alessandra; Wiggers, John
Abstract Background Despite clinical practice guidelines recommending the provision of smoking cessation care to all smokers in hospital, the provision of such care can be sub-optimal. A study was conducted to assess the impact of an intervention on the provision of smoking cessation care to nicotine-dependent smokers across a network of hospitals. Methods A 4-year interrupted time series study was undertaken in a single health district in New South Wales, Australia. A multi-component intervention was implemented over a 2-year period in all 37 public general hospitals. Outcome data were collected from eight randomly selected hospitals via medical record audit. Logistic regression analyses assessed differences between baseline, intervention and follow-up periods in the provision of seven measures of care: brief advice, offer and provision of inpatient and discharge nicotine replacement therapy, and offer and acceptance of referral to a Quitline. Results Approximately 164, 250 patients were discharged from the hospitals during the study, 16 % of whom were smokers. Of the selected smokers, 56.12 % (n = 2072) were nicotine-dependent. The prevalence of smoking cessation care increased significantly for all seven measures between baseline and intervention periods, and for six of the seven measures between the baseline and follow-up periods. The odds of receiving care at follow-up were between 1.7 (CI 1.18–2.58, p = 0.0004) and 6.2 (CI 2.84–13.85, p < 0.0001) times greater than at baseline. At follow-up, 53, 16 and 7 of smokers were offered inpatient NRT, discharge NRT and a Quitline referral, respectively. Conclusions Significant gains in the provision of smoking cessation care were indicated. However, at best, slightly more than half of the patients received smoking cessation care. Additional care enhancement strategies are required if all smokers are to obtain the intended benefits of smoking cessation care guidelines.